Applicability and Challenges of Using Machine Translation in Translator Training - Melita Koletnik Korošec (ELOPE, 2011)
During the last decade, translation as well as translator training have experienced a significant change. This change has been significantly influenced by the development of the Internet and the successive availability of web-based translation resources, such as Google Translate. Their introduction into the translation didactic process and training is no longer a matter of a teacher’s personal preference and IT skills, but a necessity imposed by the ever-swifter advancement of technology. This article presents the experimental results of an ongoing broader research study focusing on the modes and frequency of use of the Internet, Google Translate and Google Translator Toolkit among translation students at the undergraduate level. The preliminary results, presented in this article, are based on a questionnaire which was prepared in relation to the use of Google Translate while considering the latest professional findings. The article concludes with the author’s observations as to the applicability of these resources in translator training and the challenges thereof.